2018
DOI: 10.1039/c8cp03572e
|View full text |Cite
|
Sign up to set email alerts
|

How abasic sites impact hole transfer dynamics in GC-rich DNA sequences

Abstract: Changes in DNA charge transfer properties upon the creation of apurinic and apyrimidinic sites have been used to monitor DNA repair processes, given that such lesions generally reduce charge transfer yields. However, because these lesions translate into distinct intra and extrahelical conformations depending on the nature of the unpaired base and its DNA context, it is unclear the actual impact of such diverse conformations on charge transfer. Here we combine classical molecular dynamics, quantum/molecular mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Additionally, UNG creates ~45°k inks at dUTP positions (61), which facilitate the extrusion and subsequent skipping of the abasic site by a DNA damage tolerant DNA polymerase. Considering the polydypirimidine motifs, such extruded positioning could be facilitated by the relatively small flanking pyrimidine bases, in a similar fashion as was recently described for flanking cytosine bases (62). Indeed, mismatched pairs have an increased propensity for spontaneous base flipping (63), and the presence of UNG further increases the lifetime of open states following spontaneous base-pair dissociation and twists the unstacked nucleotides out of their helical conformation (64)(65)(66).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Additionally, UNG creates ~45°k inks at dUTP positions (61), which facilitate the extrusion and subsequent skipping of the abasic site by a DNA damage tolerant DNA polymerase. Considering the polydypirimidine motifs, such extruded positioning could be facilitated by the relatively small flanking pyrimidine bases, in a similar fashion as was recently described for flanking cytosine bases (62). Indeed, mismatched pairs have an increased propensity for spontaneous base flipping (63), and the presence of UNG further increases the lifetime of open states following spontaneous base-pair dissociation and twists the unstacked nucleotides out of their helical conformation (64)(65)(66).…”
Section: Discussionmentioning
confidence: 65%
“…Although AP sites, mismatched bases, and uracil residues have a particular proclivity to adopt extruded configurations (62,63,(67)(68)(69), juxtalocations could theoretically also result from spontaneous base flipping of matched base pairs, especially A-T pairs (66). Indeed, we observe that germline motifs AT and TA, which contain no cytosine bases on either strand and would therefore remain unexplained through the UNG pathway, are the least abundant reference motifs of all tandem substitutions -yet are not absent.…”
Section: Discussionmentioning
confidence: 75%
“…Accordingly, charge transport in RNA can significantly differ from that in DNA and is worth thorough investigation. However, while multiple theoretical and experimental studies addressed charge transport in DNA [16][17][18][19], such studies for RNA [14,20,21] are rare. Very recently, it was shown that charge transport along the DNA molecule plays an important role in regulation of the replication process [18] and DNA repair [19], and disruption of DNA conductivity may cause severe diseases [22].…”
Section: Of 10mentioning
confidence: 99%
“…tRNA and ribosomal RNA (rRNA) [15]. While multiple theoretical and experimental studies addressed charge transport in DNA [16][17][18][19], such studies for RNA [14,20,21] are rare. Very recently, it was shown that charge transport along the DNA molecule plays important role in regulation of the replication process [18] and DNA repair [19], and disruption of DNA conductivity may cause severe diseases [22].…”
Section: Introductionmentioning
confidence: 99%